Single keyed joints behaviour and capacity formulation under direct shear using non-linear finite-element analysis. (January 2023) - Al-Rousan, Rajai Z.; Qudaisat, Muneer S.
Abstract: Short precast box girders offer economical, safe, and serviceable structures that can be rapidly constructed. The joints between segments along the bridge span are considered locations of discontinuity that control its strength and behavior. This research aims to study the effect of lateral confinement and concrete compressive strength on the behavior of the dry single-keyed joint in precast segmental bridges under direct static shear caused by vertical load through non-linear FEA simulation. A parametric study was carried out by establishing and validating a Finite Element Analysis model in ABAQUS based on the Concrete Damage Plasticity model. The keyed joints with various combinations of compressive concrete strengths ranging from 15 MPa to 50 MPa at 5 MPa increments and confinement pressure ranging from 0 to 6 MPa at 1 MPa increments were tested. The results of the numerical analysis of the 56 combinations were produced in the form of ultimate load-carrying capacity, load–displacement curves, crack evolution, and concrete crushing evolution in the keyed zone, leading to a better understanding of the behavior and failure sequence of the mentioned joints. The increase in lateral confinement led to increasing the ultimate shear strength of the keyed dry joint as well as increasing its initial stiffness and vertical displacement at the peak load consequently. However, this enhancement ceases with lower-grade concrete strength at higher confinement levels. A new shear capacity formula was proposed and evaluated against the numerical analysis results, selected experimental work, and the current design formulas, including AASHTO. The proposed formula was shown to agree very well with mentioned experimental and numerical work.